The Role of Ultrasound and Computed Tomography in Evaluating Right Iliac Fossa Pain in Young Patients - Jainesh Toppo; Anima R. Xalxo; Rajeev K. Ranjan; Nisha Rai; Suresh K. Toppo; Abhishek Kumar; Abhay Kumar (Journal of Pharmacy and Bioallied Sciences)
Background: Right iliac fossa (RIF) pain is a common clinical presentation in young patients, with differential diagnoses ranging from appendicitis to gynecological and urological conditions. This study evaluates the role of ultrasound (USG) and computed tomography (CT) in diagnosing RIF pain. Methods: A cross-sectional study was conducted on 55 patients aged 15–35 years presenting with RIF pain. USG and CT findings were compared to identify sensitivity and specificity in diagnosing conditions such as appendicitis, ovarian cysts, and urolithiasis. Results: Appendicitis was the most common diagnosis (32.72%), followed by ovarian cysts (20%). CT demonstrated higher sensitivity and specificity than USG, particularly in detecting appendicitis and urolithiasis. Ovarian cysts were primarily diagnosed using USG. Two properly formatted tables summarize diagnostic accuracy and condition prevalence. Conclusion: CT is superior for definitive diagnosis, especially for appendicitis and urolithiasis, while USG remains essential for gynecological evaluations.